Adaptations to maintain the contributions of small-scale fisheries to food security in the Pacific Islands. (February 2018) - Bell, Johann D.; Cisneros-Montemayor, Andrés; Hanich, Quentin; Johnson, Johanna E.; Lehodey, Patrick; Moore, Bradley R.; Pratchett, Morgan S.; Reygondeau, Gabriel; Senina, Inna; Virdin, John; Wabnitz, Colette C.C.
Abstract: In several Pacific Island countries and territories (PICTs), rapid population growth and inadequate management of coastal fish habitats and stocks is causing a gap to emerge between the amount of fish recommended for good nutrition and sustainable harvests from coastal fisheries. The effects of ocean warming and acidification on coral reefs, and the effects of climate change on mangrove and seagrass habitats, are expected to widen this gap. To optimise the contributions of small-scale fisheries to food security in PICTs, adaptations are needed to minimise and fill the gap. Key measures to minimise the gap include community-based approaches to: manage catchment vegetation to reduce sedimentation; maintain the structural complexity of fish habitats; allow landward migration of mangroves as sea level rises; sustain recruitment and production of demersal fish by managing 'source' populations; and diversify fishing methods to increase catches of species favoured by climate change. The main adaptions to help fill the gap in fish supply include: transferring some fishing effort from coral reefs to tuna and other large pelagic fish by scaling-up the use of nearshore fish aggregating devices; developing fisheries for small pelagic species; and extending the shelf life of catches by improving post-harvest methods. Modelling the effects of climate change on the distribution of yellowfin tuna, skipjack tuna, wahoo and mahi mahi, indicates that these species are likely to remain abundant enough to implement these adaptations in most PICTs until 2050. We conclude by outlining the policies needed to support the recommended adaptations.